Delayed Discharges and Hospital Type: Evidence from the English NHS1. (September 2017) - Gaughan, James; Gravelle, Hugh; Siciliani, Luigi
Abstract: Delayed discharges of patients from hospital, commonly known as bed‐blocking, are a long‐standing policy concern. Delays can increase the overall cost of treatment and may worsen patient outcomes. We investigate how delayed discharges vary by hospital type (Acute, Specialist, Mental Health, Teaching) and the extent to which such differences can be explained by demography, case mix, hospital quality, the availability of long‐term care, and hospital governance as reflected in whether the hospital has Foundation Trust status, which gives greater autonomy and flexibility in staffing and pay. We use a new panel database of delays in all English NHS hospital Trusts from 2011–12 to 2013–14. Employing count data models, we find that a greater local supply of long‐term care (care‐home beds) is associated with fewer delays. Hospitals that are Foundation Trusts have fewer delayed discharges and might therefore be used as exemplars of good practice in managing delays. Mental Health Trusts have more delayed discharges than Acute Trusts, but a smaller proportion of them are attributed to the NHS, possibly indicating a relatively greater lack of adequate community care for mental health patients.